PEMBELAJARAN DARING PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Lestari, Shindy (PD PGMI se Indonesia, 2021)
Online learning in math subjects is very important to discuss so this study aims to evaluate online learning in math subjects. This study uses qualitative exploration case study method while sample technique is purposive sampling with a sample number of 45 students, 3 class teachers and 10 parents /guardians of grade V elementary school students in Pekanbaru. Data from research samples are collected through interviews and online questionnaires, so the results of this study explain the role of teachers and parents in the implementation of online learning in mathematics subjects, namely: 1) the role of teachers by creating a meaningful learning process, fun and adapted to the materials and characteristics of learners. 2) The role of parents is to guide, accompany, solve students' difficulties during home study, fostering students' learning interests. While the results of online learning evaluation in mathematics subjects show that students have difficulty focusing on understanding math materials and there are various obstacles such as on the network and the material taught is not discussed again by the teacher. As well alternative solutions for the implementation of learning in math subjects can be done by providing contextual teaching materials, creating a communicative learning environment, using varied methods, teachers and parents / guardians of students must work together and coordinate online by providing information related to their child's development during online learning at home and give creative time to students doing useful activities at home as well as the role of teachers and parents / guardians of students by providing reinforcement, motivation to students as a form of increasing interest, spirit in conducting online learning activities in math subjects.